1995
DOI: 10.1007/bf00118189
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of TPA-induced cell motility: human well-differentiated rectal adenocarcinoma cells move as coherent sheets via localized modulation of cell-cell adhesion

Abstract: We previously found that 12-O-tetradecanoylphorbol-13-acetate (TPA)-enhanced invasion of Matrigel was associated with augmentation of cell motility but not with metalloproteinase activity in a highly metastatic variant (L-10) of human rectal adenocarcinoma cell line RCM-1. In a two-dimensional cell motility assay, TPA induced active L-10 cell locomotion with characteristic morphology; the cells moved outwards from the cell islands mainly as a localized coherent sheet of cells. The leading cells showed locomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…The forces generated by cell clusters appear to be higher than those used by individual cells, as estimated from comparative measurements of the number and size of focal contacts (Kolega 1982). Similar cluster polarity and migratory persistence were confirmed for cell groups and sheets that spontaneously develop from human cancer explants invading into 3D collagen lattices (Friedl et al 1995) and well-differentiated hepatocellular carcinoma cells during their culture on fibronectin-coated surfaces (Nabeshima et al 1995).…”
Section: Historical Backgroundmentioning
confidence: 56%
See 1 more Smart Citation
“…The forces generated by cell clusters appear to be higher than those used by individual cells, as estimated from comparative measurements of the number and size of focal contacts (Kolega 1982). Similar cluster polarity and migratory persistence were confirmed for cell groups and sheets that spontaneously develop from human cancer explants invading into 3D collagen lattices (Friedl et al 1995) and well-differentiated hepatocellular carcinoma cells during their culture on fibronectin-coated surfaces (Nabeshima et al 1995).…”
Section: Historical Backgroundmentioning
confidence: 56%
“…Migrating cell sheet Embryonic keratinocytes 2D glass cover slip (Vaughan and Trinkaus 1966) Migrating cell cluster Fish melanoma cells 2D glass cover slip (Kolega 1981) Migrating cell cluster Epithelial and mesenchymal cancer explants 3D collagen lattice (Friedl et al 1995, Hegerfeldt et al 2002 Cohort migration Adenocarcinoma cells 2D fibronectin or gelatin coated surface (Nabeshima et al 2000, Nabeshima et al 1995 Collective migration Multicellular state of Dictyostelium discoideum 2D surfaces (Palsson and Othmer 2000) Branching morphogenesis; tubulogenesis Epithelial tubular cells, i.e. mammary or bronchial epithelium 3D gelatin or collagen matrices (Zegers et al 2003) Migrating cell cluster Undifferentiated cells in the blastoderm Zebrafish (in vivo) (Cooper and D'Amico 1996) (noninvoluting endocytic marginal cells)…”
Section: Termmentioning
confidence: 99%
“…Canoe is required for the proper dorsal closure in embryos (Takahashi et al, 1998;Boettner et al, 2003), a process in which collective cell migration is involved (for reviews, see Nabeshima et al, 1999;Lee and Gotlieb, 2003;Friedl, 2004;Friedl et al, 2004). Collective cell migration is characterized by the maintenance of dynamic intercellular contacts between strongly cell-cell adhesive cells that exhibit coordinated movement (Nabeshima et al, 1995;Nabeshima et al, 1997;Farooqui and Fenteany, 2005). A possible involvement of AF6 or afadin in this process has so far not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Collective migration is a well-studied phenomenon that is characteristic of embryological development, such as during the migration of cell clusters or sheets in the ectoderm following closure of the neural tube (Davidson and Keller, 1999). In vitro studies (Friedl et al, 1995;Nabeshima et al, 1995) showed that cells can migrate as a functional unit, and that in contrast to single motile cells, cell-cell adhesion can lead to a particular form of cortical actin filament present along cell junctions. This enables formation of a larger, multicellular contractile body.…”
Section: Mechanisms Of Tumor Cell Migrationmentioning
confidence: 99%
“…This enables formation of a larger, multicellular contractile body. Here, a select group of highly motile cells are designated as so-called "path-generating" cells that create migratory traction via pseudopod activity (Friedl et al, 1995;Hegerfeldt et al, 2002;Nabeshima et al, 1995). It is then believed that cells located in the inner and trailing regions are passively dragged behind during dissemination.…”
Section: Mechanisms Of Tumor Cell Migrationmentioning
confidence: 99%